Melatonin Improves Outcomes of Heatstroke in Mice by Reducing Brain Inflammation and Oxidative Damage and Multiple Organ Dysfunction. (4th December 2013) - Tian, Yu-Feng; Lin, Cheng-Hsien; Hsu, Shu-Fen; Lin, Mao-Tsun
Abstract : We report here that when untreated mice underwent heat stress, they displayed thermoregulatory deficit (e.g., animals display hypothermia during room temperature exposure), brain (or hypothalamic) inflammation, ischemia, oxidative damage, hypothalamic-pituitary-adrenal axis impairment (e.g., decreased plasma levels of both adrenocorticotrophic hormone and corticosterone during heat stress), multiple organ dysfunction or failure, and lethality. Melatonin therapy significantly reduced the thermoregulatory deficit, brain inflammation, ischemia, oxidative damage, hypothalamic-pituitary-adrenal axis impairment, multiple organ dysfunction, and lethality caused by heat stroke. Our data indicate that melatonin may improve outcomes of heat stroke by reducing brain inflammation, oxidative damage, and multiple organ dysfunction.